Resumption of germination of Brosimum gaudichaudii Trécul seeds. after natural cessation - Gama, Dráuzio Correia; Farias, Teresa Aparecida Soares de; Jesus, Geisimara Santos de; Santos, Érica Teixeira dos; Carvalho, Silvana da Costa Cunha de (Revista Ecologia e Nutrição Florestal - ENFLO, 2025)
The present study aimed to evaluate the germination potential of Brosimum gaudichaudii Trécul seeds. found pre-germinated in the field, expressing possible water memory mechanisms. In a Caatinga remnant in Bahia, seeds were collected from five B. gaudichaudii matrices in two ecophysiological conditions: pre-germinated (presenting radicles) and intact. The seeds were taken to the Seed Analysis Laboratory of the Federal University of Recôncavo da Bahia, two treatments were tested: intact seeds (SI) and pre-germinated (SG) with 10 replications of 10 seeds each. They were placed in a gerbox with humus to germinate in BOD at a temperature of 30ºC and a 12-hour photoperiod. Assessments took place daily. They were considered germinated from the formation of normal seedlings. ANOVA was performed and means were compared using the Tukey test (p<0.05) of the analyzed parameters: germination percentage-PG, average germination time-TMG and germination speed index-IVG. The SG treatment was statistically superior, with 35% compared to the SI (18%) in PG. Both treatments were statistically similar to each other in TMG (SI=25.5 days; GS=24.7 days). SG seeds were more vigorous (IVG=0.146 seeds/days) than SI (IVG=0.076). Thus, it is concluded that the B. gaudichaudii seeds are capable of resuming the germination process after a period of dehydration, without losing viability, under the ecophysiological conditions found in the Caatinga.